2014
DOI: 10.1093/mnras/stu1536
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Illustris Project: simulating the coevolution of dark and visible matter in the Universe

Abstract: We introduce the Illustris Project, a series of large-scale hydrodynamical simulations of galaxy formation. The highest resolution simulation, Illustris-1, covers a volume of (106.5 Mpc) 3 , has a dark mass resolution of 6.26 × 10 6 M , and an initial baryonic matter mass resolution of 1.26 × 10 6 M . At z = 0 gravitational forces are softened on scales of 710 pc, and the smallest hydrodynamical gas cells have an extent of 48 pc. We follow the dynamical evolution of 2 × 1820 3 resolution elements and in additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,835
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,235 publications
(1,921 citation statements)
references
References 134 publications
78
1,835
0
8
Order By: Relevance
“…The energy-driven scalings we predict are consistent with those assumed in state-of-the-art simulations that match observed properties of galaxies and the CGM (Dave et al 2013;Ford et al 2014;Genel et al 2014;Vogelsberger et al 2014). They are, however, somewhat different from that predicted by the Feedback in Realistic Galaxies (FIRE) suite of zoom simulations that also self-consistently drive outflows; the FIRE simulations find a shallower dependence for > v 60 circ km s −1 and a steeper dependence for smaller systems (Muratov et al 2015).…”
Section: Mass Loading Factor Evolutionsupporting
confidence: 76%
“…The energy-driven scalings we predict are consistent with those assumed in state-of-the-art simulations that match observed properties of galaxies and the CGM (Dave et al 2013;Ford et al 2014;Genel et al 2014;Vogelsberger et al 2014). They are, however, somewhat different from that predicted by the Feedback in Realistic Galaxies (FIRE) suite of zoom simulations that also self-consistently drive outflows; the FIRE simulations find a shallower dependence for > v 60 circ km s −1 and a steeper dependence for smaller systems (Muratov et al 2015).…”
Section: Mass Loading Factor Evolutionsupporting
confidence: 76%
“…At higher mass, it has been shown that additional feedback recipes are needed to prevent overcooling (e.g. Vernaleo & Reynolds 2006;Gabor et al 2011;Vogelsberger et al 2014;Schaye et al 2015).…”
Section: Merger Tree Selectionmentioning
confidence: 99%
“…Hence one needs to asses the relative importance of mergers versus smooth accretion driven by the cosmic environment and to study its induced morphological diversity. With the advent of large-scale albeit fairly well resolved cosmological hydrodynamical simulations such as Horizon-AGN , see as well Devriendt et al 2010;Khandai et al 2014;Vogelsberger et al 2014;Schaye et al 2015 for similar simulations performed with different numerical techniques), it has recently become feasible to investigate these different physical processes in detail and with sufficient statistics, a necessary requirement to truly unravel the impact of galaxy environment on their properties.…”
Section: Introductionmentioning
confidence: 99%